Street harassment experiences of female undergraduate students at a State University in Zimbabwe - Mawere, Daniel; Moyo, Annah (International Journal of Research and Innovation in Social Science, 2019)
The study examined street harassment experiences of female undergraduate students at a university in Gweru, Zimbabwe. Socio-cultural and socio-control theories informed the study. The research adopted a constructivist, qualitative approach. Interviews were carried out with 18 undergraduate female students between the ages of 19 to 24 years to find out the nature of street harassment they experienced, how they responded to the harassment as well as what could be done to make them move in the city without fear of harassment. The study found out that street harassment was prevalent in public transport and in the streets. Street harassment was attributed to how female students dressed as well as a general negative attitude towards them. The street harassment issue was attributed to male domination of the public space with the intention of keeping females in a subordinate position. What emerges from this study is that street harassment is a matter of concern to the female undergraduate students who feel that their freedom of movement is restricted due to consistent and persistent street harassment by men. Reporting to police does not seem to yield any positive results. If anything it brings further harassment of the participants. There is need to induct the police into the issue of street harassment by educating and empowering them about respecting girls especially those who come to report that they have been harassed. Furthermore, the participants believe that public education is a vital piece of the battle to eliminate street harassment.